Transferable skills following WAIS-II verbal comprehension index - Neer, Rosa Haydée; Lopetegui, María Susana; Rossi Casé, Lilia Elba (2007)
In this document the results and the reflections brought about by the research for the standardization of the verbal comprehension index of Wechsler scale subtests for measuring adult intelligence, WAIS -III for the general population from 16 to 24 years for the city of La Plata , using the collective administration modality are reported In this opportunity, the performance of 229 students from secondary school from 16 to 18 years, both genders, is being analyzed in the information subtest, as well as that of 155 university and non-university tertiary students from 19 to 24 years, both genders in the same subtest The information subtest is of particular interest because of the implication of previous knowledges in the text comprehension and the personal transferable skills. Given the responses, the analysis allow to make some observations a) there are no statistically significant differences between the individual and the collective administration, by gender and b) the average of correct responses for both age groups is the same but the score distribution shows a greater homogeneity in the group from 16 to18 years.
Keywords: WAIS III; Verbal comprehension index; Information; Collective administration